Exploring the relationship between cortical GABA concentrations, auditory gamma‐band responses and development in ASD: Evidence for an altered maturational trajectory in ASD. Issue 4 (1st October 2016) - Port, Russell G.; Gaetz, William; Bloy, Luke; Wang, Dah‐Jyuu; Blaskey, Lisa; Kuschner, Emily S.; Levy, Susan E.; Brodkin, Edward S.; Roberts, Timothy P.L.
Abstract : Autism spectrum disorder (ASD) is hypothesized to arise from imbalances between excitatory and inhibitory neurotransmission (E/I imbalance). Studies have demonstrated E/I imbalance in individuals with ASD and also corresponding rodent models. One neural process thought to be reliant on E/I balance is gamma‐band activity (Gamma), with support arising from observed correlations between motor, as well as visual, Gamma and underlying GABA concentrations in healthy adults. Additionally, decreased Gamma has been observed in ASD individuals and relevant animal models, though the direct relationship between Gamma and GABA concentrations in ASD remains unexplored. This study combined magnetoencephalography (MEG) and edited magnetic resonance spectroscopy (MRS) in 27 typically developing individuals (TD) and 30 individuals with ASD. Auditory cortex localized phase‐locked Gamma was compared to resting Superior Temporal Gyrus relative cortical GABA concentrations for both children/adolescents and adults. Children/adolescents with ASD exhibited significantly decreased GABA+/Creatine (Cr) levels, though typical Gamma. Additionally, these children/adolescents lacked the typical maturation of GABA+/Cr concentrations and gamma‐band coherence. Furthermore, children/adolescents with ASD additionally failed to exhibit the typical GABA+/Cr to gamma‐band coherence association. This altered coupling during childhood/adolescence may result in Gamma decreases observed in the adults with ASD. Therefore, individuals with ASD exhibit improper local neuronal circuitry maturation during a childhood/adolescence critical period, when GABA is involved in configuring of such circuit functioning. Provocatively a novel line of treatment is suggested (with a critical time window); by increasing neural GABA levels in children/adolescents with ASD, proper local circuitry maturation may be restored resulting in typical Gamma in adulthood. Autism Res 2017, 10: 593–607 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.